COVID-19, Pre-Eclampsia, and Complement System - Agostinis, Chiara; Mangogna, Alessandro; Balduit, Andrea; Aghamajidi, Azin; Ricci, Giuseppe; Kishore, Uday; Bulla, Roberta (Frontiers in Immunology, 2021)
COVID-19 is characterized by viral-induced injury leading to multi-organ failure, together with inflammatory reaction, endothelial cell (EC) injury, and prothrombotic coagulopathy with thrombotic events. Complement system via its cross-talk with contact and coagulation systems contributes significantly to the severity and pathological consequences due to SARS-CoV-2 infection. These immunopathological mechanisms overlap in COVID-19 and pre-eclampsia (PE). Thus, mothers contracting SARS-CoV-2 infection during pregnancy are more vulnerable to developing PE. SARS-CoV-2 infection of ECs, via its receptor ACE2 and co-receptor TMPRSS2, can lead to endothelial dysfunction and disruption of vascular integrity, causing hyperinflammation and hypercoagulability. This is aggravated by bradykinin increase due to inhibition of ACE2 activity by the virus. Complement system is important for the progression of normal pregnancy, and its dysregulation can impact in the form of PE-like syndrome as a consequence of SARS-CoV-2 infection. Thus, there is also an overlap between treatment regimens of COVID-19 and PE. Complement inhibitors, especially targeting C3 or MASP-2, are exciting options for treating COVID-19 and consequent PE. In this review, we examine the role of complement, contact and coagulation systems as well as endothelial hyperactivation with respect to SARS-CoV-2 infection during pregnancy and likely development of PE.